2021
DOI: 10.1039/d1qi00314c
|View full text |Cite
|
Sign up to set email alerts
|

Electron belt-to-σ-hole switch of noncovalently bound iodine(i) atoms in dithiocarbamate metal complexes

Abstract: Co-crystallization of the dithiocarbamate complexes [MII(S2CNEt2)2] (M = Cu 1, Ni 2, Pd 3, Pt 4) and 1,3,5-triiodotrifluorobenzene (FIB) gives an isomorphic series of (1–4)∙2FIB co-crystals exhibiting the quadruple Cu/Ni/Pd/Pt...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 110 publications
3
45
0
Order By: Relevance
“…However, recently the QTAIM approach has been combined with other approaches, such as the NCIPlot analysis. [46,49] Predominantly, XRD structure coordinates were employed for subsequent theoretical studies, [46,48,50] while in some instances the theoretical approaches used only model complexes, for example, I•••Co(I) and I•••Au(À 1). [51][52][53] In the following subsections, we inspected the appropriate geometrical parameters and computationally analyzed the XRD structures involving structure-directing σ-hole•••d[M] interactions for the occurrence of HaBs and highlighted applications of these interactions for HaB-involving crystal engineering.…”
Section: σ-Hole•••m Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently the QTAIM approach has been combined with other approaches, such as the NCIPlot analysis. [46,49] Predominantly, XRD structure coordinates were employed for subsequent theoretical studies, [46,48,50] while in some instances the theoretical approaches used only model complexes, for example, I•••Co(I) and I•••Au(À 1). [51][52][53] In the following subsections, we inspected the appropriate geometrical parameters and computationally analyzed the XRD structures involving structure-directing σ-hole•••d[M] interactions for the occurrence of HaBs and highlighted applications of these interactions for HaB-involving crystal engineering.…”
Section: σ-Hole•••m Interactionsmentioning
confidence: 99%
“…Several examples of Pt II -involved HaBs have been found and discussed in the literature, thus demonstrating the ability of platinum(II) square-planar complexes to participate in this type of metal-involving unconventional HaB. [43,47,49,50,71,[80][81][82][83][84][85] acceptor. Agreeably, the MEP surface plot represented in Figure 10(c) demonstrates that the MEP value above and below the platinum(II) center is larger in its absolute value than that at the palladium(II) atom (Figure 8c), and thus it is more suitable as an acceptor for the occurrence of σ-hole interactions.…”
Section: Platinum(ii)mentioning
confidence: 99%
“…We used the equation E = 0.556*V r to estimate the association energy of each HaB. This equation has been successfully used before in a variety of halogen bonding interactions [41][42][43][44][45][46][47][48][49]. As a result, the association energy of HaB "a" is −1.67 kcal/mol, HaB "b" is −0.78, and HaB "c" is −0.88 kcal/mol.…”
Section: Dft Calculationsmentioning
confidence: 99%
“… 17 , 18 Further works of van Koten et al showed that the analogous palladium and nickel NCN pincer complexes interact with diiodine in other ways. 19 21 Nevertheless, later works represented metal-involving XB not only with Pt II 22 − 28 and Pd II 23 , 27 , 29 , 30 but also with Ni II , 27 , 31 Rh I , 32 , 33 Au I , 34 36 and Au 0 centers 37 41 as nucleophiles.…”
Section: Introductionmentioning
confidence: 99%